2014
DOI: 10.1115/1.4027431
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanics of Fatigue and Fracture in Teeth

Abstract: Tooth fracture is a major concern in the field of restorative dentistry. However, knowledge of the causes for tooth fracture has developed from contributions that are largely based within the field of mechanics. The present manuscript presents a technical review of advances in understanding the fracture of teeth and the fatigue and fracture behavior of their hard tissues (i.e., dentin and enamel). The importance of evaluating the fracture resistance of these materials, and the role of applied mechanics in deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
62
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 152 publications
(267 reference statements)
2
62
0
3
Order By: Relevance
“…The authors did not specify the contributions according to the size scales but only according to the mechanisms. Unbroken mineral ligaments have the highest contribution to toughening of enamel with bridging stress intensity between 0.2 and 0.6 MPa m 0.5 , which is approximately 25% of the global toughness in their study [7,13]. The reduction in the local stress intensity factor induced by bridging of organic matrix was estimated to be 0.1 MPa m 0.5 .…”
Section: (E) Hierarchical Level 4: Schmelzmuster (I) Structural Featuresmentioning
confidence: 93%
See 2 more Smart Citations
“…The authors did not specify the contributions according to the size scales but only according to the mechanisms. Unbroken mineral ligaments have the highest contribution to toughening of enamel with bridging stress intensity between 0.2 and 0.6 MPa m 0.5 , which is approximately 25% of the global toughness in their study [7,13]. The reduction in the local stress intensity factor induced by bridging of organic matrix was estimated to be 0.1 MPa m 0.5 .…”
Section: (E) Hierarchical Level 4: Schmelzmuster (I) Structural Featuresmentioning
confidence: 93%
“…Identifying the features that enable this performance in biological materials with the aim of implementing them to improve engineering materials has become an increasingly important area over many years. This has resulted in renewed interest with further enamel studies employing advanced fracture mechanics being published [7][8][9][10][11][12][13]. These authors reported that bulk enamel exhibits increasing fracture toughness with crack extension (R-curve behaviour) compared with brittle materials that generally have a single value of fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The covering enamel of the tooth resists tooth fracture to a great extent due to its complex microstructure and decussation of enamel rods. Decussation of enamel rods deflects cracks and prevents them from reaching the dentino-enamel junction (Yahyazadehfar et al 2013, Yahyazadehfar et al 2014). If the crack reaches the dentino-enamel junction it well serve as the second defense line against tooth fracture (Dong et .…”
Section: Introductionmentioning
confidence: 99%
“…Human teeth are very resilient but covered with enamel which is a brittle material (Yahyazadehfar et al 2014). They are designed to withstand loads up to 700 n for repeated millions of cycles during life (Anusavice 1996, p. 90-91, Okiyama et al 2003).…”
Section: Introductionmentioning
confidence: 99%